"DE NOVO" TRISOMY OF THE SHORT ARM OF CHROMOSOME 9 (9P TRISOMY). CASE REPORT - Doina Maria Ioan; Mariana Moiceanu (Amaltea Medical Publishing House, 2009)
The authors report the case of a 2 year 9 month old girl with neurodevelopmental delay and dysmorphic facial features: microcephaly, high and arched forehead, proeminence of the metopic suture, enophtalmya, micrognatia, big and malformed ears with low insertion. Classic Cytogenetic analysis with G banding revealed the following chromosomial formula: 46, XX de r(15)(9p ter ® 9p 11::15p 12 ® 15q ter), meaning that some additional material that correspond to the short arm of chromosome 9 is translocated to the 15 chromosome. The FISH test confirmed the presence of triplication in this patient. Normal karyotype was present in parents and sibling.